Review on 3D Facial Animation Techniques - Adibah Najihah Mat Noor, Noor; Mohd Suaib, Norhaida; Anwar Ahmad, Muhammad; Ahmad, Ibrahim (International Journal of Engineering and Technology, 2018)
Generating facial animation has always been a challenge towards the graphical visualization area. Numerous efforts had been carried out in order to achieve high realism in facial animation. This paper surveys techniques applied in facial animation targeting towards realistic facial animation. We discuss the facial modeling techniques from different viewpoints; related geometric-based manipulation (that can be further categorized into interpolations, parameterization, muscle-based and pseudoâ€“muscle-based model) and facial animation techniques involving speech-driven, image-based and data-captured. The paper will summarize and describe the related theories, strength and weaknesses for each technique.Â